Factors Affecting Stock Prices with EPS as Moderating Variable Among Manufacturing Companies - Madeline Nathania; Henryanto Wijaya (International Journal of Application on Economics and Business, 2023)
The goal of this study is to look at the impact of liquidity, profitability, and also solvency towards the stock prices in manufacturing businesses issued on the Indonesia Stock Exchange (IDX) starting from 2018 to 2020, utilizing Earnings per Share (EPS) as a moderating variable. In order to gain samples for the research, we used descriptive quantitative with purposive sampling technique. The data collected contains 210 samples, including 70 manufacturing enterprises that were listed on the IDX from 2018 to 2020. Moderated Regression Analysis (MRA) is used in conjunction with EViews 10 software to process the data. MRA is used to model the case because in MRA, the regression equation contains interaction element between variables to know if the effect of a moderating variable is getting stronger or weaker. The findings reveal that both liquidity and profitability brings a advantageous and large impact towards stock prices, whereas solvency and EPS have a negative and minor impact, and that EPS can mitigate the impact of profitability, liquidity, and solvency in relation to stock prices. This study's implications include the need to enhance a company's performance and financial situation so that its financial statements are sound and stock prices rise, which is, of course, a good sign for investors.